AKTIVITAS ANTIOKSIDAN DAN SIFAT SENSORIDARI NASI INSTAN HASIL HIDROLISIS PATI YANG DIPERKAYA DENGAN EKSTRAK PEGAGAN (Centella asiatica) [Antioxidant Activity and Sensory Properties from Starch Hydrolysis of Instant Rice Enriched with Pegagan Leaf Extract (Centella asiatica)] - Sri Hidayati; Samsu Udayana Nurdin; Ryan Ajie Nugroho (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2016)
This aim of the research was to obtain an optimal concentration of Centella asiatica [H1] extract were added in processing instant rice in order to obtain low levels of digestibility starch, with high antioxidant activity and the best sensory properties. The results showed that the best treatment was found in instant rice with the addition of Centella asiatica [H2] leaf extract at 15%. This instant rce has the characteristics of starch hydrolysis rate of 15.50%, the antioxidant activity was 67,876%, total of phenolic content was 0,271 ppm GAE, the percentage of panelists with gave ‘like criteria’ to rice aroma, taste color and texture were 12,22%, 24,44%, 13,33% and 22,22%.Keywords : antioxidant activity, pegagan, phenolic content, starch hydrolysis. [H1]italic [H2]h4